The Relationship Between Peer Influence and E-Cigarette use Among Students - Herfina. S; Nur Inayah Ismaniar; Mujtahidah (Science Tech Group, 2026)
. E-cigarette use is a growing trend among students and has attracted attention due to its health impacts. This behavior is influenced not only by individual factors but also by social factors, particularly peer groups, including social interactions, peer habits, and group solidarity. The purpose of this study was to determine the relationship between social interactions, peer habits, and group solidarity with e-cigarette use among students at the Faculty of Sport and Health Sciences, Universitas Negeri Makassar (FIKK UNM). The research method used was a quantitative study with an observational analytical design using a cross-sectional study approach. The population in this study was all 1,446 students from the 2023 intake of FIKK UNM, with a sample size of 330 respondents obtained using the Slovin formula. Data were collected using a questionnaire and analyzed using the chi-square test in SPSS. The results showed that the majority of respondents (199 respondents (60.3%) did not use e-cigarettes, while 131 (39.7%) did use e-cigarettes. The results of the bivariate analysis showed a relationship between social interaction and e-cigarette use (p = 0.001), a relationship between peer habits and e-cigarette use (p = 0.001), and a relationship between group solidarity and e-cigarette use (p = 0.001). The conclusion of this study indicates that peers play a significant role in e-cigarette use in students. This influence occurs through social interaction, similar processes to friends' habits, and the drive to maintain group solidarity. Therefore, prevention efforts are needed that focus not only on the individual but also on the student's social environment. These findings contribute to the achievement of SDG 3 (Good Health and Well-Being) and SDG 4 (Quality Education) by highlighting the importance of community-based interventions within academic institutions to promote healthier behaviors among the younger generation.